2022
DOI: 10.1111/ctr.14619
|View full text |Cite
|
Sign up to set email alerts
|

Center variations in patient selection for simultaneous heart‐kidney transplantation

Abstract: There are no established regulations governing patient selection for simultaneous heart‐kidney (SHK) transplantation, creating the potential for significant center‐level variations in clinical practice. Methods Using the United Network for Organ Sharing (UNOS) Standard Transplant Analysis and Research (STAR) file, we examined practice trends and variations in patient selection for SHK at the center level between January 1, 2004 and March 31, 2019. Results Overall, SHK is becoming more common with most centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In contrast, overutilization of sHK is a silent event that carries little penalties. A recent UNOS registry analysis demonstrated that the adjusted odds of sHK varied 57‐fold between the highest and lowest sHK performing centers, and the median baseline eGFR in sHK recipients ranged from 19 to 59 mL/min/1.73 m 2 3 . This significant practice variation in patient selection led to the recent establishment and approval of national policies for combined heart‐kidney allocation by the Organ Procurement and Transplantation Network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, overutilization of sHK is a silent event that carries little penalties. A recent UNOS registry analysis demonstrated that the adjusted odds of sHK varied 57‐fold between the highest and lowest sHK performing centers, and the median baseline eGFR in sHK recipients ranged from 19 to 59 mL/min/1.73 m 2 3 . This significant practice variation in patient selection led to the recent establishment and approval of national policies for combined heart‐kidney allocation by the Organ Procurement and Transplantation Network.…”
Section: Discussionmentioning
confidence: 99%
“…Significant kidney disease predicts morbidity and mortality after heart transplantation, 1 and simultaneous heart‐kidney transplants (sHK) may be indicated in selected patients. Although the use of sHK has increased significantly in the United States in the last two decades, 2 the appropriate patient selection remains challenging, leading to considerable variability in practice between regions and institutions 3 . Besides the difficulty of distinguishing potentially reversible kidney injury from intrinsic, advanced kidney disease, the decision for sHK is further complicated by the ethical dilemma of appropriate donor organ allocation, as sHK takes donor kidneys away from patients with end‐stage kidney disease awaiting isolated kidney transplants 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite constituting only around 7% of the heart transplant volume, the number of heart–kidney transplants (HKT) have steadily increased over the past decade [1 ▪▪ ]. Nationwide, there is significant center-dependent variability in patient selection for simultaneous HKT [2 ▪▪ ,3 ▪ ]. The estimated glomerular filtration rate (eGFR) for those listed for DOT varied from 19 to 59 ml/min/1.73 m 2 .…”
Section: Heart–kidney Transplantationmentioning
confidence: 99%
“…Of multiorgan transplants, sHK transplants have experienced the largest increase in frequency from 2015 to 2020 ( 7 ). This has occurred even though debate exists regarding the exact population of patients that would benefit from dual organ transplantation, and there is notable variability in kidney function of sHK recipients by center, with median estimated glomerular filtration rate (eGFR) ranging from 19 to 59 ml/min/1.73 m 2 from 2014 to 2019 ( 8 ). This debate, and resulting variability, is driven by the inability to predict the potential for renal recovery in patients with heart failure or recovery of heart function in patients with renal failure.…”
Section: Cardiorenal Syndrome and Shk Transplantationmentioning
confidence: 99%